Sistem akaun belum terima bersepadu Pejabat Bendahari - Abu Bakar, Bebe (2003)
Many organization are adopting an integrated approach to implement and manage important elements of their revenue stream activities and to provide value added service to customers. Yet, the current billing procedure in the University has caused problems especially in tracing the issued bills and the weaknesses in record keeping. Realizing the importance of reporting revenue and debts in accurate and timely manner to the management and customer, the author propose an integrated account receivable application be developed to solve the problem. Besides, this system is capable of generating standardized bills and eliminate bad debts. The thesis focuses to analyze the best concept and features of the accounting packages available in the market, to be included in the new application design. The new system will be designed using the waterfall approach, 2-tier architecture and SQL Server databases.